Does open enrollment policy improve academic performance among students involved with child protective service? Findings from Minnesota-linking information for kids. (January 2020) - Hong, Saahoon; Choi, Won Seok; Piescher, Kristine N.; Zhang, Yanchen; Rhee, Taeho Greg
Highlights: Open enrollment (OE) policy was designed to provide educationally disadvantaged students with equal access to schools with enriched education resources. Our findings suggest that OE allowed students with history of child protection service (CPS) to have better academic resources. However, there was no association between OE and achievement. Abstract: The open enrollment (OE) policy was designated to provide educationally disadvantaged students with equal access to schools with enriched educational resources that enhance student learning. Comparative analysis and linear mixed modeling with propensity score matching were used to identify the extent to which students involved with child protection service (CPS) utilized an inter-district open enrollment option and to examine their academic achievement before and after switching schools. Results indicated that open enrollment provided students involved with CPS better academic resources from neighboring schools that have better academic outcomes. However, students involved with CPS did not have significant improvement on academic performance by utilization of open enrollment. The results suggest that while the intent of the policy led to use the OE option among students involved with CPS, additional support and non-school-based resources may be needed to improve academic achievements.